Continuous Real-time Monitoring of Patient’s Vital Signs Based on ZigBee Standard - Saso Koceski; Olivera Kotevska; Elena Vlahu-Gjorgievska; Vladimir Trajkovik (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
This paper gives an understanding of what possibilities Wireless Body Area Network (WBAN) have when using shortrange wireless communications protocols. There advantages are used to facilitate versatility in the movements of health care patients. The paper investigates the feasibility of using the ZigBee protocol, givean analysis of methods for collection of received data from multi sensor environment, and mechanisms for privacy and data protection by using encryption techniques. This characteristics are applied on previously developed collaborative healthcare system model (COHESY).COHESY is aimed at continuous real time remote patients’ health monitoring.